Authors (The Biblical archaeology review, 2020)
Yosef Garfinkel ("The Face of Yahweh?") is the Yigael Yadin Chair in Archaeology of Israel at the Hebrew University of Jerusalem. In addition to publishing the results of his excavations at Khirbet Qeiyafa, he currently directs excavations at Tel Lachish and Khirbet Arai.